Transfer Pricing Policy: The Role of Taxes, Incentive Tunneling and Bonus Mechanism - Elfaumi Farkhah Elfa; Agus Ismaya Hasanudin; Tri Lestari Lestari (PT. EQUATOR SINAR AKADEMIA, 2022)
This study aims to determine and examine the effect of taxes, tunneling incentive, and bonus mechanism for transfer pricing indications. The approach used in research is a quantitive approach. The population in this study uses registered manufacturing companies on the Indonesia Stock Exchange in 2016-2020. The number of samples in this research used after going through purposive sampling technique as many as 14 companies for 5 year. The data in this study are secondary data and data obtained from the site www.idx.go.id and company performance reports. The analytical method used in this study is multiple linier regression analysis with using SPSS Statistics 25 software in data processing starting from descriptive statistical tests to hypothesis testing. The results showed that the tax have an effect on indications of transfer pricing. And tunneling incentives have an effect on indications of transfer pricing. Meanwhile the variable bonus mechanism has no effect on transfer pricing indications.